2004
DOI: 10.1111/j.1439-0418.2004.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the infestation ratio of spiny bollworm (Earias insulana) and pink bollworm (Pectinophora gossypiella) on cotton yield grown in semi‐arid region of Turkey

Abstract: Field studies were conducted in Harran Plain, Turkey, to investigate the infestation of spiny bollworm (SBW) and pink bollworm (PBW) in cotton blind bolls during the period 1999-2001. Blind bolls left on the cotton plants after the harvest were collected, and the PBW and SBW larvae, which are the causes of infection were counted in the laboratory by splitting the bolls. The statistical methods reveal that the infestation ratio variable plays an important role in reducing cotton yield. The infestation ratio var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
2
Order By: Relevance
“…The direct effect of the technique on cotton yield has been demonstrated and the addition of the difficulties of conventional control of PBW, support the view that this technique should be adopted by the entire body of local farmers. Unlu and Bilgic (2004) suggested that a 1% increase in the infestation rate of PBW caused a 2.5% yield loss of cotton. This study revealed that the MD technique provided a 10% decrease in the infestation rate, and therefore its contribution to the cotton yield is easily understood.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The direct effect of the technique on cotton yield has been demonstrated and the addition of the difficulties of conventional control of PBW, support the view that this technique should be adopted by the entire body of local farmers. Unlu and Bilgic (2004) suggested that a 1% increase in the infestation rate of PBW caused a 2.5% yield loss of cotton. This study revealed that the MD technique provided a 10% decrease in the infestation rate, and therefore its contribution to the cotton yield is easily understood.…”
Section: Discussionmentioning
confidence: 98%
“…PBW was found by Karman (1960) in southern Turkey, while the first report in the current study area was in 1997 by Ozpinar et al (1998). Although it was a new pest for the area, the damage was economically important (Unlu 2003) and it was noted that a 1% increase in infestation ratio of PBW would reduce the cotton yield by approximately 2.5-6% (Unlu and Bilgic 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The amount and frequency of monitoring required for decision making depends upon the crop and its insects (Thomas 1999;Se´tamou et al 2000). Almost invariably, uniformity of insect infestations does not occur, so it is essential to take a representative sample that overcomes the lack of uniformity (Unlu and Bilgic 2004). Also, it is important to make a representative survey of a field in the least amount of time (Radcliffe 2002).…”
Section: Monitoring In Ipmmentioning
confidence: 99%
“…Les pics de captures les plus importants ont été observés pour les localités de Bouaké, Niakara et Boundiali pratiquement à la même période (Août-Octobre-Novembre). La présence simultanée du ravageur dans les trois localités pourrait s'expliquer par la présence d'individus sédentaires qui contrairement aux migrateurs ont la possibilité d'entrer en diapause puis de reprendre leur développement lorsqu'ils sont en présence de conditions favorables (Unlu and Bilgic, 2004 Les différentes périodes de pics et de baisse d'activité des papillons adultes pourraient être en rapport avec le stade phénologique des cotonniers dans chaque localité. A ces dates, les parcelles peuvent présenter un environnement propice à l'apparition et à la multiplication de P. gossypiella dont les premiers pics coïncident avec la phase de formations des organes fructifères des cotonniers (Attique et al, 2004).…”
Section: Période Critique De Pullulations Des Populations Adultes Et unclassified